Ketevan World Sacred Music Festival : a musical experience of coexistence - Salas, Sándor M. (Anandor Producciones, 2016)
The documentary record of the first edition of the Ketevan World Sacred Music Festival, held in Goa (India) is transformed in these frames into a celebration of what music unites and distinguishes as cultural ferment.--